2019
DOI: 10.35301/ksme.2019.22.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence End-of-Life Care Provided by Nurses in General Hospitals

Abstract: Nurses often play key roles in providing end-of-life care. The purpose of this study is to examine the factors that influence end-of-life care delivered by nurses in South Korea. As a method, a cross-sectional descriptive survey design was applied. The data were collected through self-reported questionnaires from 233 nurses working at intensive care units and medical-surgical wards of general hospitals in Seoul and the Gyeonggi Province. The structured questionnaires measured end-of-life care performance, know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
1
1
Order By: Relevance
“…The performance of end-of-life care was significantly higher among nurses in general wards compared to those in ICUs. This finding contradicts previous studies that found no significant differences between internal/surgical wards and ICUs [ 25 ], and similar levels in oncology departments and ICUs, with a higher level observed in emergency departments [ 11 ]. Unlike these earlier studies, the scale used in our research incorporated items related to family assessment and communication.…”
Section: Discussioncontrasting
confidence: 99%
“…The performance of end-of-life care was significantly higher among nurses in general wards compared to those in ICUs. This finding contradicts previous studies that found no significant differences between internal/surgical wards and ICUs [ 25 ], and similar levels in oncology departments and ICUs, with a higher level observed in emergency departments [ 11 ]. Unlike these earlier studies, the scale used in our research incorporated items related to family assessment and communication.…”
Section: Discussioncontrasting
confidence: 99%
“…However, nurses have been found to suffer from negative emotions such as ethical conflicts, guilt, and depression while processing and implementing WLST [ 6 ]. This negative sentiment was reported to impair nurses’ ability to respect patients’ right to self-determination and recognize their role in WLST, resulting in improper provision of medical care for patients on their deathbeds [ 7 , 8 ]. Therefore, it is imperative for nurses to have positive attitudes toward WLST before practicing WLST-related nursing care.…”
Section: Introductionmentioning
confidence: 99%